Effect of Health Education on Healthy Nutrition and Physical Activity among Female Teachers Aged 40–60 Years in Asmara, Eritrea: A Quasiexperimental Study - Helen Gebretatyos; Soliana Amanuel; Lidia Ghirmai; Ghidey Gebreyohannes; Eyasu H. Tesfamariam (Journal of Nutrition and Metabolism)
Background. Middle age is a period in women’s life where many changes occur in their bodies due to the decline of gonadotropins. As a result, they face various vasomotor, psychological, and somatic symptoms. Moreover, chronic illness such as diabetes, hypertension, heart diseases, and osteoporosis are prevalent at this time. Healthy nutrition and physical activity are effective factors to reduce the problems of menopause faced during middle age. Objective. This study aimed at assessing the effect of health education on healthy nutrition and physical activity among 40–60-year-old female teachers in elementary, junior, and secondary schools of Asmara. Method. A quasiexperimental design was used in this study. The data were collected from 99 middle-age female teachers who were selected by stratified random sampling. The intervention was conducted using lecture, brochure, and group discussion for a total of 3 hours. Data on physical activity and healthy nutrition were collecting using HPLP- II subscales physical activity and nutrition. Sociodemographic data were collected using a predesigned questionnaire. The effect of educational training at preintervention and postintervention was evaluated by the paired t-test and factorial mixed ANOVA using SPSS (version 22). Results. The mean score of practicing healthy diet and physical activity at preintervention and postintervention was 27/44 (SD = 4.20) and 31/44 (SD = 5.36), respectively. A significant difference in the scores of practicing healthy diet and physical activity was observed after the educational intervention (MD = 4.06, 95% CI 2.95–5.17, p<0.0001). The effectiveness of health education was seen across the categories of age, educational level, and occupational level where none of them showed significant interaction, displaying similar effect of educational intervention across all categories of the demographic variables. Conclusion. The structured educational intervention was beneficial for the studied women in changing their practice on healthy nutrition and physical activity.